2020
DOI: 10.1080/17520843.2020.1720264
|View full text |Cite
|
Sign up to set email alerts
|

Inflation expectations of households: do they influence wage-price dynamics in India?

Abstract: This paper examines the usefulness of survey based measures of inflation expectations to predict inflation using hybrid versions of New Keynesian Phillips Curve (NKPC). While both 3-months ahead and 1-year ahead inflation expectations of households emerge statistically significant in explaining and predicting inflation in India, effectively they work as substitutes of backward looking expectations given that household expectations are found to be largely adaptive. Unlike in other countries, this paper does not… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…While the former used an autoregressive moving average (ARMA) framework for the analysis of the data on inflation expectations, the latter used hybrid versions of NKPC to examine the usefulness of survey-based inflation expectations to predict inflation. Pattanaik et al (2020) also used ARDL and a vector error correction model for gauging the influence of household inflation expectations on wage-setting behavior in India. They both highlighted the role of anchored inflation expectations by the central banks in the effectiveness of the monetary policy.…”
Section: Review Of Literaturementioning
confidence: 99%
See 1 more Smart Citation
“…While the former used an autoregressive moving average (ARMA) framework for the analysis of the data on inflation expectations, the latter used hybrid versions of NKPC to examine the usefulness of survey-based inflation expectations to predict inflation. Pattanaik et al (2020) also used ARDL and a vector error correction model for gauging the influence of household inflation expectations on wage-setting behavior in India. They both highlighted the role of anchored inflation expectations by the central banks in the effectiveness of the monetary policy.…”
Section: Review Of Literaturementioning
confidence: 99%
“…Patra and Ray (2010) and Pattanaik et al (2020) found the vital role of inflation expectations in conducting monetary policy and their reflection on the credibility of the central banks. While the former used an autoregressive moving average (ARMA) framework for the analysis of the data on inflation expectations, the latter used hybrid versions of NKPC to examine the usefulness of survey-based inflation expectations to predict inflation.…”
Section: Introductionmentioning
confidence: 99%
“…With the change in its policy target to IT, now the question arises that, given India’s low-income level where households spend a substantial part of their income on food and fuel, can the RBI accurately forecast its inflation path so as to contain it within a predefined range. This is because food and fuel inflation are volatile, given the fact that India is heavily dependent on monsoon and crude import for its food and fuel needs, respectively (Banerjee et al, 2020; Bhattacharya & Sen Gupta, 2018; Pattanaik et al, 2020). Moreover, a large part of the Indian economy is in the informal sector that makes monetary transmission difficult (Anand et al, 2016; Benes et al, 2017; Kulshreshtha, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…4 Our analysis looks specifically at the role played by domestic factors, and whether inflation expectations have become more anchored since early 2015. We contribute to the literature that analyses the determinants of inflation in India (Anand, Ding, and Tulin (2014); Sonna and others (2014); Behera, Wahi and Kapur (2018); Pattanaik, Muduli, and Ray (2019))-a more expansive discussion of the literature is provided in section 2 of this paper. Although these studies have looked at headline and foodprice inflation processes in India, our paper focuses more on any changes in the inflation process since the adoption of FIT.…”
Section: Introductionmentioning
confidence: 99%